Adhesive sheet
The adhesive sheet addresses the challenge of bonding members with steps and curved surfaces by using a laminate structure with differently strong adhesive layers, achieving effective contour following and reworkability.
Patent Information
- Application Number
- JP2022034720
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-07
- Publication Date
- 2025-05-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing adhesive sheets struggle to adequately follow the steps and curved surfaces of members during bonding, leading to issues such as gaps and poor optical properties.
A pressure-sensitive adhesive sheet with a laminate structure, where the first and second adhesive layers have different adhesive strengths and are designed to have specific pushing rates, allowing the sheet to effectively follow the contours of members with steps and curved surfaces while maintaining reworkability.
The adhesive sheet achieves excellent step and curved surface followability, along with good reworkability, ensuring high product yield and appearance quality even when bonding complex-shaped members.
Smart Images

Figure 2025069474000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive sheet. [Background technology]
[0002] Displays having liquid crystal elements, light-emitting diode (LED) elements, organic electroluminescence (OLED) elements, etc., and optical products having lenses have laminates in which the components that make up the display or optical product are stacked together.
[0003] A laminate of such members is generally formed by bonding one member to another member using the adhesive layer of a pressure-sensitive adhesive sheet.
[0004] Furthermore, in the case of mobile electronic devices such as smartphones, add-on components such as cases and films may be attached or mounted to the mobile electronic devices for the purposes of adding design features and protecting the mobile electronic devices.
[0005] When bonding such components together, bonding defects can occur due to misalignment during bonding, leading to lower product yields and poor appearance, etc. Therefore, when bonding defects occur, particularly when bonding expensive and inexpensive components together, or when bonding and installing additional components, the inexpensive components or the additional components may be peeled off and reused (reworked).
[0006] Therefore, pressure-sensitive adhesive sheets used for bonding such components are required to have not only adhesive properties to ensure good bonding, but also the ability to be peeled off and reused after bonding (reworkability).
[0007] Patent Document 1 discloses that a double-sided adhesive tape used for attaching a film having a resin layer formed thereon to a sensor glass is provided with adhesive properties to resin and removability from glass. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2015-131924 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, components constituting a display body or optical product, or add-on components, may have steps or curved shapes for the purpose of imparting design features, achieving specified optical characteristics, etc.
[0010] When bonding a component having a step or a curved surface, the adhesive layer of the adhesive sheet needs to conform to the step and curved surface of the component. If the adhesive layer cannot conform to the step and curved surface sufficiently, a space (floating, peeling, etc.) where the adhesive is not in contact with the component occurs near the step or in the curved surface, resulting in problems such as a decrease in optical properties and a poor appearance.
[0011] The present invention has been made in consideration of the above-described circumstances, and aims to provide an adhesive sheet including an adhesive layer that can adequately conform to the steps and curved surfaces of components and has good reworkability, even when bonding components having steps or curved shapes. [Means for solving the problem]
[0012] The aspects of the present invention are as follows. [1] A pressure-sensitive adhesive sheet having a laminate in which a first pressure-sensitive adhesive layer and a second pressure-sensitive adhesive layer are laminated, When the surface of the laminate facing the first pressure-sensitive adhesive layer is designated as side A and the surface facing the second pressure-sensitive adhesive layer is designated as side B, the adhesive strength of side A is greater than the adhesive strength of side B, When side A is continuously pressed at a pressing speed of 0.01 mm / sec, the pressing depth at which the pressing load reaches 5 N is defined as the side A pressing depth, and when side B is continuously pressed at a pressing speed of 0.01 mm / sec, the pressing depth at which the pressing load reaches 5 N is defined as the side B pressing depth, the side A pressing ratio, which is the side A pressing depth relative to the thickness of the laminate, and the side B pressing ratio, which is the side B pressing depth relative to the thickness of the laminate, are 35% or more.
[0013] [2] The pressure-sensitive adhesive sheet according to [1], wherein the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer are in contact with each other in the laminate.
[0014] [3] The pressure-sensitive adhesive sheet according to [1] or [2], wherein the B-side indentation ratio is greater than the A-side indentation ratio.
[0015] [4] An adhesive sheet according to any one of [1] to [3], wherein the ratio of the adhesive strength of side A to the adhesive strength of side B is within the range of 2 or more and 10,000 or less.
[0016] [5] The pressure-sensitive adhesive sheet according to any one of [1] to [4], wherein the thickness of the first pressure-sensitive adhesive layer is 30 μm or more and 800 μm or less.
[0017] [6] The pressure-sensitive adhesive sheet according to any one of [1] to [5], wherein the thickness of the second pressure-sensitive adhesive layer is 10 μm or more and 300 μm or less.
[0018] [7] The pressure-sensitive adhesive sheet according to any one of [1] to [6], wherein the first pressure-sensitive adhesive layer is made of an acrylic pressure-sensitive adhesive and the second pressure-sensitive adhesive layer is made of a urethane pressure-sensitive adhesive.
[0019] [8] The pressure-sensitive adhesive sheet according to any one of [1] to [7], wherein the pressure-sensitive adhesive sheet has a release sheet disposed on side A and a release sheet disposed on side B. Effect of the Invention
[0020] According to the present invention, it is possible to provide a pressure-sensitive adhesive sheet including a pressure-sensitive adhesive layer that can sufficiently conform to the steps and curved surfaces of components and has good reworkability, even when bonding components having steps or curved shapes. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a schematic cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram for explaining the pressing rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present invention will be described in detail below based on specific embodiments.
[0023] (1. Adhesive sheet) As shown in Fig. 1, the pressure-sensitive adhesive sheet 1 according to this embodiment has a laminate 10 in which a first pressure-sensitive adhesive layer 11 and a second pressure-sensitive adhesive layer 12 are laminated. Furthermore, as long as the effects of the present invention can be obtained, the pressure-sensitive adhesive sheet 1 may have components other than the laminate 10. In this embodiment, for example, as shown in Fig. 1, two release sheets 21 and 22 are disposed on the surface of the laminate 10 so as to sandwich the laminate 10 in order to protect the laminate 10 until the pressure-sensitive adhesive sheet is used.
[0024] The pressure-sensitive adhesive sheet according to the present embodiment is preferably used for bonding members having a stepped and / or curved surface. One of the members to be bonded may have a stepped and / or curved surface, or both of the members to be bonded may have a stepped and / or curved surface.
[0025] An example of an adhesive sheet having good reworkability is an adhesive sheet having a structure in which an adhesive layer exhibiting strong adhesive strength and an adhesive layer exhibiting weak adhesive strength are laminated together, as disclosed in Patent Document 1.
[0026] With such an adhesive sheet, when two components are bonded together via the adhesive layer of the adhesive sheet, the component bonded to the adhesive layer exhibiting strong adhesive strength can be easily peeled off together with the adhesive sheet from the component bonded to the adhesive layer exhibiting weak adhesive strength.
[0027] However, when a member has a step and / or a curved surface, the entire pressure-sensitive adhesive layer needs to be significantly deformed during lamination to conform to the step and / or the curved surface. In this case, there is a problem that the combination of a pressure-sensitive adhesive layer with high adhesive strength and a pressure-sensitive adhesive layer with low adhesive strength cannot sufficiently conform to the step and / or the curved surface, or good reworkability cannot be obtained.
[0028] In order to address the above problems, in the pressure-sensitive adhesive sheet according to the present embodiment, the physical properties of the laminate composed of at least two pressure-sensitive adhesive layers are controlled. The components of the pressure-sensitive adhesive sheet according to the present embodiment are described in detail below.
[0029] (1.1. Laminate) The laminate according to the present embodiment has a first pressure-sensitive adhesive layer and a second pressure-sensitive adhesive layer. The laminate adheres members to each other by the adhesive strength exerted by the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer. The laminate according to the present embodiment may have layers other than the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer, but the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer are located as the outermost layers in the laminate. That is, it is preferable that the surfaces facing each other in the thickness direction of the laminate coincide with the exposed main surface of the first pressure-sensitive adhesive layer and the exposed main surface of the second pressure-sensitive adhesive layer.
[0030] The thickness of the laminate according to the present embodiment is preferably 30 to 1000 μm, more preferably 60 to 700 μm, further preferably 100 to 500 μm, particularly preferably 120 to 300 μm, and more preferably 140 to 200 μm, which makes it easier to satisfy the physical properties related to the pressing ratio and adhesive strength, which will be described later, and also improves handleability.
[0031] The thickness of the first pressure-sensitive adhesive layer constituting the laminate according to this embodiment is preferably 30 μm or more and 800 μm or less. This makes it easier to satisfy the physical properties related to the pressing ratio and adhesive strength, which will be described later, and improves handleability. From this viewpoint, the thickness is preferably 40 to 500 μm, more preferably 50 to 300 μm, even more preferably 55 to 200 μm, and particularly preferably 60 to 130 μm.
[0032] The thickness of the second pressure-sensitive adhesive layer constituting the laminate according to this embodiment is preferably 10 μm or more and 300 μm or less. This makes it easier to satisfy the physical properties related to the pressing ratio and adhesive strength, which will be described later, and improves handleability. From this viewpoint, the thickness is preferably 20 to 200 μm, more preferably 30 to 160 μm, even more preferably 40 to 120 μm, and particularly preferably 50 to 90 μm.
[0033] In the laminate according to the present embodiment, the ratio of the thickness of the first pressure-sensitive adhesive layer to the thickness of the second pressure-sensitive adhesive layer is preferably 0.01 to 1.4, more preferably 0.05 to 1.3, even more preferably 0.1 to 1.2, even more preferably 0.3 to 1.1, and most preferably 0.5 to 1. When the ratio is within the above range, it becomes easier to satisfy the physical properties related to the pressing ratio and adhesive strength, which will be described later, and handleability tends to be good.
[0034] In the laminate according to the present embodiment, it is preferable that there is no layer other than the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer (i.e., a layer located between the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer), but there may be cases where a layer other than the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer is provided within a range that does not impair the effects of the present invention. In this case, the thickness of the layer is preferably 1 to 200 μm, more preferably 20 to 100 μm. This improves the handleability of the laminate.
[0035] Specific conditions for measuring the above thickness will be described later in the Examples.
[0036] In this embodiment, by controlling the following physical properties of the laminate, when a component having a stepped and / or curved shape is bonded to the laminate, the pressure-sensitive adhesive layer conforms well to the stepped and / or curved shape of the component, and the component can be easily peeled off (reworked) after bonding.
[0037] (1.2. Physical properties of laminate) The laminate according to this embodiment has the following physical properties. In the following, of the surfaces of the laminate, the surface on the first pressure-sensitive adhesive layer side is referred to as surface A, and the surface on the second pressure-sensitive adhesive layer side is referred to as surface B. In Fig. 1, surface 10a of laminate 10 (surface 11a of first pressure-sensitive adhesive layer 11) is surface A, and surface 10b of laminate 10 (surface 12b of second pressure-sensitive adhesive layer 12) is surface B.
[0038] (1.2.1. Push-in rate) In this embodiment, the indentation ratios of the A and B sides are controlled. The indentation ratio is calculated as the ratio of the indentation depth to the thickness of the laminate. As shown in Fig. 2, the indentation depth is the indentation depth h at the time when the indentation load becomes 5 N when the surface of the laminate 10 (A sides 10a, 11a in Fig. 2) is continuously indented at a indentation speed of 0.01 mm / sec.
[0039] Here, when side A is continuously pressed at a pressing speed of 0.01 mm / sec, the pressing depth at the time when the pressing load becomes 5 N is defined as the side A pressing depth, and the side A pressing depth relative to the thickness of the laminate is defined as the side A pressing rate (%). For example, when the thickness of the laminate is 200 μm and the side A pressing depth is 50 μm, the side A pressing rate is 25%.
[0040] Similarly, when side B is continuously pressed at a pressing speed of 0.01 mm / sec, the pressing depth at the time when the pressing load reaches 5 N is defined as the side B pressing depth. The side B pressing depth relative to the thickness of the laminate is defined as the side B pressing rate (%).
[0041] In this embodiment, both the A-side indentation ratio and the B-side indentation ratio are 35% or more. The indentation ratio reflects the resistance of the laminate to stress that causes deformation, and the higher the indentation ratio, the lower the resistance of the laminate to deformation. As a result, even if the pressure-sensitive adhesive layer deforms to conform to steps, curved surfaces, etc., the laminate is likely to maintain the conforming state.
[0042] Therefore, by setting the A-side pressing ratio and the B-side pressing ratio within the above ranges, even when a laminate having a first pressure-sensitive adhesive layer and a second pressure-sensitive adhesive layer is attached to a member having an uneven surface and / or a curved surface, it can sufficiently conform to the uneven surface and / or the curved surface.
[0043] From the above viewpoints, the A-side pressing ratio is preferably 35% or more, more preferably 38% or more, and even more preferably 40% or more. The B-side pressing ratio is preferably 35% or more, more preferably 38% or more, even more preferably 40% or more, and particularly preferably 42% or more. On the other hand, the upper limits of the A-side pressing ratio and the B-side pressing ratio are not particularly limited, but in this embodiment, from the viewpoint of maintaining the shape of the pressure-sensitive adhesive sheet, the upper limits of the A-side pressing ratio and the B-side pressing ratio are 80%.
[0044] Also, the B-side indentation ratio is preferably greater than the A-side indentation ratio. The indentation ratio does not reflect the properties of the first or second adhesive layer alone, but reflects the properties of the entire laminate. When an indentation load is applied to the first adhesive layer during measurement of the indentation depth, for example, since the second adhesive layer is located directly below the first adhesive layer, the deformation of the first adhesive layer is alleviated, but since there is a hard table directly below the second adhesive layer, the deformation of the second adhesive layer is not alleviated as much. Therefore, if the adhesive layer constituting the surface opposite to the surface to which the indentation load is applied is easily deformed, the indentation ratio increases.
[0045] That is, the B-side pressing ratio being greater than the A-side pressing ratio means that the first pressure-sensitive adhesive layer is more easily deformed than the second pressure-sensitive adhesive layer. From this viewpoint, the first pressure-sensitive adhesive layer is more easily conformable to steps and / or curved surfaces. More specifically, the B-side pressing ratio being greater than the A-side pressing ratio means that the value obtained by subtracting the A-side pressing ratio from the B-side pressing ratio is greater than 0 points. The value is preferably greater than 0 points, more preferably 1 point or more, and even more preferably 1.4 points or more.
[0046] The pressing rate can be adjusted, for example, by changing the composition of the adhesive, the molecular weight of the main polymer that constitutes the adhesive, the structure of the adhesive, the viscoelasticity of the adhesive, the layer structure in the laminate, the thickness of each layer that constitutes the laminate, etc.
[0047] The pressing rate can be measured by a method that applies a load to the adhesive layer that corresponds to the magnitude of deformation that the adhesive layer undergoes when following a step and / or a curved surface, and can evaluate the deformation of the entire adhesive layer. Since the adhesive layer is greatly deformed when following a step and / or a curved surface, a method that can apply a relatively large load and measure the deformation of the entire adhesive layer is preferable. The measurement method for calculating the pressing rate will be described in the examples.
[0048] In the laminate according to the present embodiment, the A-side indentation depth is preferably 10 μm or more, more preferably 30 μm or more, even more preferably 50 μm or more, preferably 60 μm or more, and more preferably 66 μm or more, from the viewpoint of being able to adjust the above-mentioned indentation ratio to a desired range. On the other hand, the upper limit of the A-side indentation depth is equal to or less than the upper limit of the thickness of the laminate, which allows the pressure-sensitive adhesive sheet to maintain its shape and exhibit the desired performance. And, from the viewpoint of being able to adjust the above-mentioned indentation ratio to a desired range, the A-side indentation depth is preferably 150 μm or less, more preferably 120 μm or less, even more preferably 90 μm or less, preferably 78 μm or less, and more preferably 72 μm or less.
[0049] In the laminate according to the present embodiment, the B-side indentation depth is preferably 10 μm or more, more preferably 35 μm or more, even more preferably 55 μm or more, preferably 65 μm or more, and of these, preferably 70 μm or more, from the viewpoint of being able to adjust the above-mentioned indentation ratio to a desired range. On the other hand, the upper limit of the B-side indentation depth is equal to or less than the upper limit of the thickness of the laminate, which allows the pressure-sensitive adhesive sheet to maintain its shape and exhibit the desired performance. And, from the viewpoint of being able to adjust the above-mentioned indentation ratio to a desired range, the B-side indentation depth is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 110 μm or less, preferably 90 μm or less, and of these, preferably 80 μm or less.
[0050] (1.2.2.Adhesion) In the laminate according to this embodiment, it is preferable that the adhesive strength of the A side of the laminate to the soda lime glass (A side adhesive strength) is different from the adhesive strength of the B side of the laminate to the soda lime glass (B side adhesive strength), and it is preferable that the A side adhesive strength is greater than the B side adhesive strength. By providing such a difference in adhesive strength, the second adhesive layer is more likely to exhibit removability (reworkability).
[0051] In this embodiment, the adhesive strength of the A-side of the laminate to soda lime glass (A-side adhesive strength) is preferably 5 N / 25 mm. That is, the adhesive strength of the first adhesive layer to soda lime glass is preferably 5 N / 25 mm or more. When the A-side adhesive strength is within the above range, the laminate can easily maintain a state in which it conforms to steps and / or curved surfaces.
[0052] From the above viewpoints, the A-side adhesive strength is more preferably 15 to 100 N / 25 mm, further preferably 30 to 80 N / 25 mm, particularly preferably 40 to 70 N / 25 mm, and of these, preferably 45 to 60 N / 25 mm.
[0053] In this embodiment, the adhesive strength of side B of the laminate to soda lime glass (side B adhesive strength) is preferably 3 N / 25 mm or less. That is, the adhesive strength of the second adhesive layer to soda lime glass is preferably 3 N / 25 mm or less. When the side B adhesive strength is within the above range, the bonded state between the first and second members can be easily released (excellent reworkability).
[0054] From the above viewpoints, the B-side adhesive strength is more preferably 0.01 to 2 N / 25 mm, further preferably 0.02 to 1 N / 25 mm, particularly preferably 0.05 to 0.6 N / 25 mm, and of these, preferably 0.08 to 0.2 N / 25 mm.
[0055] Furthermore, in this embodiment, the ratio of the adhesive strength of side A to the adhesive strength of side B (adhesive strength of side A / adhesive strength of side B) is preferably within the range of 2 to 10000. By having this ratio within the above range, it is possible to achieve a high level of compatibility between the ability to conform to uneven surfaces and / or curved surfaces and reworkability.
[0056] The ratio of the A-side adhesive strength to the B-side adhesive strength is more preferably 10-5000, further preferably 100-1200, particularly preferably 200-800, and of these, 400-600 is preferred.
[0057] Specific conditions for measuring the A-side adhesive strength and B-side adhesive strength will be described later in the Examples.
[0058] The total light transmittance of the laminate in this embodiment is preferably 70% or more, more preferably 85% or more, particularly preferably 95% or more, and even more preferably 99% or more. As a result, the laminate has excellent transparency, so that even when it follows a step or a curved surface, the member using the laminate exhibits an excellent appearance. The upper limit of the total light transmittance is usually 100% or less. The total light transmittance in this specification is a value measured in accordance with JIS K7361-1:1997, and specific measurement conditions will be described later in the examples.
[0059] The haze value of the laminate in this embodiment is preferably 5% or less, more preferably 3% or less, particularly preferably 1% or less, even more preferably 0.6% or less, and more preferably 0.4% or less. As a result, the laminate has excellent transparency, so that the member using the laminate has an excellent appearance even when it follows a step or a curved surface. The lower limit of the haze value is usually 0% or more. The haze value in this specification is a value measured in accordance with JIS K7136:2000, and specific measurement conditions will be described later in the examples.
[0060] (1.3. Composition of Adhesive) The laminate according to the present embodiment is not particularly limited in composition of the adhesive constituting the first adhesive layer and the second adhesive layer as long as it has the above-mentioned physical properties. For example, acrylic adhesives, urethane adhesives, polyester adhesives, rubber adhesives, and silicone adhesives are exemplified. The adhesive may be any of emulsion type, solvent type, and solventless type. Furthermore, the adhesive may or may not have a crosslinked structure.
[0061] In this embodiment, from the viewpoint of ease of realizing the above-mentioned physical properties and from the viewpoints of adhesive properties, optical properties, etc., the first adhesive constituting the first adhesive layer is preferably an acrylic adhesive, and the second adhesive constituting the second adhesive layer is preferably a urethane adhesive. In the following, a case where the first adhesive is an acrylic adhesive and the second adhesive is a urethane adhesive will be described.
[0062] (1.3.1. First adhesive) In this embodiment, the first adhesive is an acrylic adhesive, and more preferably an acrylic adhesive having a crosslinked structure. Specifically, the adhesive is preferably an adhesive obtained by crosslinking an adhesive composition (hereinafter sometimes referred to as "adhesive composition P1") containing a (meth)acrylic acid ester polymer (A) and a crosslinking agent (B). Such an adhesive is likely to satisfy the above-mentioned physical properties and is likely to provide good adhesive strength. In this specification, (meth)acrylic acid means both acrylic acid and methacrylic acid. The same applies to other similar terms. In addition, the term "polymer" also includes the concept of "copolymer."
[0063] (1.3.1.1. (Meth)acrylic acid ester polymer (A)) In this embodiment, the (meth)acrylic acid ester polymer (A) preferably contains, as a monomer unit constituting the polymer, a reactive group-containing monomer having in the molecule a reactive group that reacts with the crosslinking agent (B). The reactive group derived from the reactive group-containing monomer reacts with the crosslinking agent (B) to form a crosslinked structure (three-dimensional network structure), thereby obtaining a pressure-sensitive adhesive having the desired cohesive strength.
[0064] Preferred examples of the reactive group-containing monomer include a monomer having a hydroxyl group in the molecule (hydroxyl group-containing monomer), a monomer having a carboxyl group in the molecule (carboxyl group-containing monomer), a monomer having an amino group in the molecule (amino group-containing monomer), etc. Among these, a hydroxyl group-containing monomer or a carboxyl group-containing monomer having excellent reactivity with the crosslinking agent (B) is preferred, and a hydroxyl group-containing monomer is particularly preferred.
[0065] Examples of hydroxyl group-containing monomers include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate.
[0066] Among these, from the viewpoint of the reactivity of the hydroxyl group in the resulting (meth)acrylic acid ester polymer (A) with the crosslinking agent (B) and copolymerizability with other monomers, a (meth)acrylic acid hydroxyalkyl ester having a hydroxyalkyl group having 1 to 4 carbon atoms is preferred. Specifically, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, etc. are preferred, and 2-hydroxyethyl acrylate or 4-hydroxybutyl acrylate are particularly preferred. These may be used alone or in combination of two or more.
[0067] Examples of the carboxyl group-containing monomer include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. Among them, acrylic acid is preferred in terms of the reactivity of the carboxyl group in the resulting (meth)acrylic acid ester polymer (A) with the crosslinking agent (B) and copolymerizability with other monomers. These may be used alone or in combination of two or more.
[0068] Examples of the amino group-containing monomer include aminoethyl (meth)acrylate, n-butylaminoethyl (meth)acrylate, etc. These may be used alone or in combination of two or more.
[0069] The (meth)acrylic acid ester polymer (A) preferably contains 1 to 50 mass% of reactive group-containing monomer as a monomer unit constituting the polymer, more preferably 5 to 40 mass%, even more preferably 8 to 30 mass%, particularly preferably 10 to 25 mass%, and especially preferably 12 to 18 mass%. This allows a good crosslinked structure to be formed in the resulting pressure-sensitive adhesive, and a desired cohesive force is obtained. This in turn makes it easier to satisfy the above-mentioned physical properties such as the indentation ratio and adhesive strength, and improves the step-following ability and curved surface-following ability.
[0070] It is also preferable that the (meth)acrylic acid ester polymer (A) does not contain a carboxyl group-containing monomer as a monomer unit constituting the polymer. Since a carboxyl group is an acid component, by not containing a carboxyl group-containing monomer, even if the target to which the pressure-sensitive adhesive is applied includes a material that may be damaged by acid, such as a transparent conductive film or a metal film, such as tin-doped indium oxide (ITO), the damage caused by the acid (corrosion, change in resistance, etc.) can be suppressed.
[0071] However, it is permissible to contain a predetermined amount of a carboxyl group-containing monomer to the extent that the above-mentioned inconvenience does not occur. Specifically, it is permissible to contain, as a monomer unit, a carboxyl group-containing monomer in an amount of 0.1% by mass or less, preferably 0.01% by mass or less, and more preferably 0.001% by mass or less in the (meth)acrylic acid ester polymer (A).
[0072] The (meth)acrylic acid ester polymer (A) preferably contains a (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer. This allows the polymer to exhibit good flexibility and adhesion. The alkyl group may be linear or branched.
[0073] From the viewpoint of adhesion, the (meth)acrylic acid alkyl ester is preferably a (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20. Examples of the (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20 include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, and stearyl (meth)acrylate.
[0074] Among these, from the viewpoint of further improving adhesion, (meth)acrylic acid esters having an alkyl group carbon number of 1 to 8 are preferred, methyl (meth)acrylate, n-butyl (meth)acrylate or 2-ethylhexyl (meth)acrylate are particularly preferred, and n-butyl acrylate or 2-ethylhexyl acrylate are even more preferred. These may be used alone or in combination of two or more kinds.
[0075] The (meth)acrylic acid ester polymer (A) preferably contains 40 to 99% by mass or more of (meth)acrylic acid alkyl ester as a monomer unit constituting the polymer, more preferably 50 to 90% by mass or more, and even more preferably 60 to 80% by mass or more. This allows the (meth)acrylic acid ester polymer (A) to exhibit suitable flexibility and adhesion, which in turn makes it easier to satisfy the physical properties such as the above-mentioned pressing ratio and adhesive strength, resulting in good step conformability and curved surface conformability. In addition, a suitable amount of other monomer components such as reactive functional group-containing monomers can be introduced into the (meth)acrylic acid ester polymer (A).
[0076] It is also preferable that the (meth)acrylic acid ester polymer (A) contains a monomer having an alicyclic structure in the molecule (an alicyclic structure-containing monomer) as a monomer unit constituting the polymer. Since the alicyclic structure-containing monomer is bulky, it is presumed that the presence of this in the polymer increases the distance between the polymers, and the resulting adhesive can have excellent flexibility. This makes it easier to satisfy the physical properties such as the above-mentioned pressing ratio and adhesive strength, and improves the step-following ability and curved surface-following ability.
[0077] The carbon ring of the alicyclic structure in the alicyclic structure-containing monomer may be a saturated structure or may have an unsaturated bond in a part thereof. The alicyclic structure may be a monocyclic alicyclic structure or a polycyclic alicyclic structure such as a bicyclic or tricyclic structure. From the viewpoint of making the distance between the obtained (meth)acrylic acid ester polymer (A) appropriate and imparting high stress relaxation properties to the adhesive, the alicyclic structure is preferably a polycyclic alicyclic structure (polycyclic structure). Furthermore, in consideration of the compatibility of the (meth)acrylic acid ester polymer (A) with other components, the polycyclic structure is particularly preferably a bicyclic to tetracyclic structure. Also, from the viewpoint of imparting stress relaxation properties as described above, the carbon number of the alicyclic structure (meaning the total carbon number of the portion forming the ring, and when multiple rings exist independently, means the total carbon number) is usually preferably 5 or more, more preferably 7 or more. On the other hand, the upper limit of the carbon number of the alicyclic structure is not particularly limited, but from the viewpoint of compatibility as described above, it is preferably 15 or less, and particularly preferably 10 or less.
[0078] Specific examples of the alicyclic structure-containing monomer include cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, adamantyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, and dicyclopentenyloxyethyl (meth)acrylate.
[0079] Among these, dicyclopentanyl (meth)acrylate (alicyclic structure carbon number: 10), adamantyl (meth)acrylate (alicyclic structure carbon number: 10) or isobornyl (meth)acrylate (alicyclic structure carbon number: 7) are preferred, as they exhibit superior adhesion, and isobornyl (meth)acrylate is particularly preferred, with isobornyl acrylate being even more preferred. These may be used alone or in combination of two or more.
[0080] When the (meth)acrylic acid ester polymer (A) contains an alicyclic structure-containing monomer as a monomer unit constituting the polymer, the alicyclic structure-containing monomer is preferably contained in an amount of 1 to 30 mass % or more, more preferably 3 to 25 mass %, further preferably 5 to 20 mass %, and particularly preferably 8 to 15 mass %. This makes it easier to satisfy the physical properties such as the above-mentioned pressing ratio and adhesive strength, and improves the step-following ability and curved surface-following ability.
[0081] It is also preferred that the (meth)acrylic acid ester polymer (A) contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer. By making the nitrogen atom-containing monomer exist as a constituent unit in the polymer, a predetermined polarity is imparted to the adhesive, and it can be made to have excellent affinity even for an adherend having a certain degree of polarity. As the nitrogen atom-containing monomer, from the viewpoint of imparting an appropriate rigidity to the (meth)acrylic acid ester polymer (A), a monomer having a nitrogen-containing heterocycle is preferred. In addition, from the viewpoint of increasing the degree of freedom of the portion derived from the nitrogen atom-containing monomer in the higher-order structure of the adhesive that is constituted, it is preferred that the nitrogen atom-containing monomer does not contain a reactive unsaturated double bond group other than one polymerizable group used in polymerization to form the (meth)acrylic acid ester polymer (A).
[0082] Examples of monomers having a nitrogen-containing heterocycle include N-(meth)acryloylmorpholine, N-vinyl-2-pyrrolidone, N-(meth)acryloylpyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-(meth)acryloylaziridine, aziridinylethyl (meth)acrylate, 2-vinylpyridine, 4-vinylpyridine, 2-vinylpyrazine, 1-vinylimidazole, N-vinylcarbazole, and N-vinylphthalimide.
[0083] Among these, N-(meth)acryloylmorpholine is preferred, and N-acryloylmorpholine is particularly preferred, as it exhibits superior adhesive strength. These may be used alone or in combination of two or more.
[0084] When the (meth)acrylic acid ester polymer (A) contains a nitrogen atom-containing monomer as a monomer unit constituting the polymer, the nitrogen atom-containing monomer is preferably contained in an amount of 1 to 30 mass%, more preferably 2 to 20 mass%, further preferably 3 to 10 mass%, and particularly preferably 4 to 8 mass% or less. This makes it easier to satisfy the physical properties such as the above-mentioned pressing ratio and adhesive strength, and improves the step-following ability and curved surface-following ability.
[0085] The (meth)acrylic acid ester polymer (A) may contain other monomers as monomer units constituting the polymer, if desired. As the other monomers, monomers not containing reactive functional groups are preferred so as not to inhibit the above-mentioned action of the reactive functional group-containing monomer. Examples of such monomers include (meth)acrylic acid alkoxyalkyl esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, vinyl acetate, and styrene. These may be used alone or in combination of two or more.
[0086] The (meth)acrylic acid ester polymer (A) is preferably a linear polymer, which is expected to facilitate entanglement of molecular chains and improve cohesive strength, making it easier to satisfy the above-mentioned physical properties such as the indentation ratio and adhesive strength, resulting in good conformability to unevenness and curved surface.
[0087] In addition, the (meth)acrylic acid ester polymer (A) is preferably a solution polymer obtained by a solution polymerization method. By using a solution polymer, a high molecular weight polymer can be easily obtained, and the cohesive force can be expected to be improved, so that the physical properties such as the above-mentioned pressing ratio and adhesive strength can be easily satisfied, resulting in good step conformability and curved surface conformability.
[0088] The polymerization mode of the (meth)acrylic acid ester polymer (A) may be a random copolymer or a block copolymer.
[0089] The weight average molecular weight of the (meth)acrylic acid ester polymer (A) is preferably 200,000 to 2,000,000, more preferably 300,000 to 1,600,000, even more preferably 400,000 to 1,200,000, particularly preferably 450,000 to 900,000, and particularly preferably 500,000 to 700,000. This makes it easier to satisfy the physical properties such as the above-mentioned indentation ratio and adhesive strength, and improves the step-following ability and curved surface-following ability. The weight average molecular weight in this specification is a value measured by gel permeation chromatography (GPC) in terms of standard polystyrene.
[0090] In the pressure-sensitive adhesive composition P1, the (meth)acrylic acid ester polymer (A) may be used alone or in combination of two or more kinds.
[0091] (1.3.1.2. Crosslinker (B)) The crosslinking agent (B) crosslinks the (meth)acrylic acid ester polymer (A) by heating the pressure-sensitive adhesive composition P, and can satisfactorily form a three-dimensional network structure. This improves the cohesive strength of the resulting pressure-sensitive adhesive, making it easier to satisfy the physical properties such as the above-mentioned pressing ratio and adhesive strength, and improving the step-following ability and curved surface-following ability.
[0092] The crosslinking agent (B) may be any that reacts with the reactive group possessed by the (meth)acrylic acid ester polymer (A), and examples thereof include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, amine-based crosslinking agents, melamine-based crosslinking agents, aziridine-based crosslinking agents, hydrazine-based crosslinking agents, aldehyde-based crosslinking agents, oxazoline-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, and ammonium salt-based crosslinking agents.
[0093] Among these, it is preferable to use an isocyanate-based crosslinking agent that has excellent reactivity with the reactive group of the (meth)acrylic acid ester polymer (A). The crosslinking agent (B) may be used alone or in combination of two or more.
[0094] The isocyanate-based crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate, alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate, and biuret and isocyanurate forms thereof, as well as adducts which are reactants with low-molecular active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil.
[0095] Examples of epoxy crosslinking agents include 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, N,N,N',N'-tetraglycidyl-m-xylylenediamine, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane diglycidyl ether, diglycidylaniline, diglycidylamine, etc. Among these, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane is preferred from the viewpoint of reactivity with carboxy groups.
[0096] The content of the crosslinking agent (B) in the pressure-sensitive adhesive composition P1 is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, further preferably 0.1 to 2 parts by mass, and particularly preferably 0.2 to 1 part by mass, relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A). This allows the resulting pressure-sensitive adhesive to exhibit good cohesive strength, making it easier to satisfy the physical properties such as the above-mentioned indentation ratio and adhesive strength, and improving the step-following ability and curved surface-following ability.
[0097] (1.3.1.3. Other Additives) The adhesive composition P1 may contain other additives as necessary. Examples of such additives include silane coupling agents, ultraviolet absorbers, antistatic agents, tackifiers, antioxidants, light stabilizers, rust inhibitors, infrared absorbers, colorants, softeners, fillers, and refractive index adjusters. Note that polymerization solvents and dilution solvents described below are not included in the additives constituting the adhesive composition P1.
[0098] Of the above, the pressure-sensitive adhesive composition P1 preferably contains a silane coupling agent, which improves adhesion to the adherend.
[0099] The silane coupling agent is preferably an organosilicon compound having at least one alkoxysilyl group in the molecule, which has good compatibility with the (meth)acrylic acid ester polymer (A) and has optical transparency.
[0100] Examples of such silane coupling agents include polymerizable unsaturated group-containing silicon compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, and methacryloxypropyltrimethoxysilane; epoxy structure-containing silicon compounds such as 3-glycidoxypropyltrimethoxysilane and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; mercapto group-containing silicon compounds such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-mercaptopropyldimethoxymethylsilane. Examples of such silanes include amino group-containing silicon compounds such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, and 3-isocyanatepropyltriethoxysilane, or condensates of at least one of these with alkyl group-containing silicon compounds such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane. These may be used alone or in combination of two or more.
[0101] The content of the silane coupling agent in the pressure-sensitive adhesive composition P is preferably 0.05 to 2 parts by mass, more preferably 0.10 to 1 part by mass, and even more preferably 0.20 to 0.5 parts by mass, relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A). This improves the adhesion to the adherend, makes it easier to satisfy the physical properties such as the adhesive strength described above, and improves the ability to conform to unevenness and curved surfaces.
[0102] (1.3.2. Second Adhesive) In this embodiment, the second adhesive is a urethane adhesive, and a urethane adhesive having a crosslinked structure is more preferable. Specifically, it is preferable to manufacture the second adhesive using polyurethane polyol and a polyisocyanate crosslinking agent. Such an adhesive is likely to satisfy the physical properties such as the above-mentioned pressing ratio and adhesive strength, and can particularly provide good reworkability.
[0103] The polyurethane polyol is obtained by reacting a polyol with a polyisocyanate so that the equivalent ratio of isocyanate groups to hydroxyl groups is less than 1. As the polyol, polyester polyol, polyether polyol, etc. are preferable. As the polyether polyol, for example, polypropylene glycol, polyethylene glycol, polytetramethylene glycol, etc. are preferable.
[0104] The average number of functional groups per molecule of the polyether polyol is preferably 2.2 to 3.4, more preferably 2.3 to 3.3, and even more preferably 2.4 to 3.2. The number average molecular weight (Mn) of the polyether polyol is preferably 300 to 7000, and more preferably 350 to 6000.
[0105] Examples of polyisocyanates constituting polyurethane polyol include aromatic polyisocyanates, aliphatic polyisocyanates, araliphatic polyisocyanates, alicyclic polyisocyanates, etc. Also included are their trimethylolpropane adducts, biurets, nurates, etc. Examples of aromatic polyisocyanates include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, etc.
[0106] The polymerization reaction between the polyol and the polyisocyanate is generally carried out using a catalyst, such as a tin-based organometallic compound such as dioctyltin dilaurate.
[0107] On the other hand, examples of the polyisocyanate crosslinking agent include the above-mentioned trimethylolpropane adducts, biurets, nurates, etc. The amount of the polyisocyanate crosslinking agent to be blended with the polyurethane polyol is preferably such that the equivalent ratio of the isocyanate groups to the hydroxyl groups is 0.5 or more and 1.5 or less.
[0108] The adhesive composition P2 may contain other additives as necessary. As such additives, the same additives as those in the first adhesive can be used.
[0109] (1.4. Release sheet) The release sheets 21 and 22 protect the laminate 10 until the adhesive sheet 1 is used, and are peeled off when the adhesive sheet 1 (laminate 10) is to be used. In the adhesive sheet 1 according to this embodiment, one or both of the release sheets 21 and 22 are not necessarily required.
[0110] Examples of the release sheet include polyethylene films, polypropylene films, polybutene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polyethylene naphthalate films, polybutylene terephthalate films, polyurethane films, ethylene vinyl acetate films, ionomer resin films, ethylene-(meth)acrylic acid copolymer films, ethylene-(meth)acrylic acid ester copolymer films, polystyrene films, polycarbonate films, polyimide films, and fluororesin films. Crosslinked films of these films are also used. Furthermore, laminated films of these films may be used.
[0111] The release surface of the release sheet (particularly the surface in contact with the first adhesive layer and the second adhesive layer) is preferably subjected to a release treatment. Examples of the release agent used in the release treatment include alkyd-based, silicone-based, fluorine-based, unsaturated polyester-based, polyolefin-based, and wax-based release agents. It is preferable that one of the release sheets is a heavy release type release sheet with a large release force, and the other is a light release type release sheet with a small release force.
[0112] There is no particular limitation on the thickness of the release sheet, but it is usually about 20 to 150 μm.
[0113] (1.5. Production of adhesive composition) The adhesive composition P1 for preparing the first adhesive can be produced, for example, by first producing a (meth)acrylic acid ester polymer (A) and then mixing the resulting (meth)acrylic acid ester polymer (A) with a crosslinking agent (B). Additives may be added as necessary.
[0114] The (meth)acrylic acid ester polymer (A) can be produced, for example, by polymerizing a mixture of monomers constituting the polymer by a normal radical polymerization method. The polymerization of the (meth)acrylic acid ester polymer (A) can be carried out by a solution polymerization method using a polymerization initiator as necessary. By polymerizing the (meth)acrylic acid ester polymer (A) by the solution polymerization method, it becomes easy to increase the molecular weight of the obtained polymer and adjust the molecular weight distribution, and further it becomes possible to reduce the generation of low molecular weight substances.
[0115] Examples of the polymerization solvent used in the solution polymerization method include ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, methyl ethyl ketone, etc. The polymerization solvent may be used alone or in combination of two or more kinds.
[0116] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more of them may be used in combination. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].
[0117] Examples of organic peroxides include benzoyl peroxide, t-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butyl peroxyneodecanoate, t-butyl peroxypivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide.
[0118] In the above polymerization step, the weight average molecular weight of the resulting polymer can be adjusted by adding a chain transfer agent such as 2-mercaptoethanol.
[0119] Next, the crosslinking agent (B) and the dilution solvent are added to the obtained solution of the (meth)acrylic acid ester polymer (A) and mixed thoroughly to obtain the adhesive composition P1 (coating solution) diluted with the solvent. If necessary, additives may be added.
[0120] In addition, when any of the above components is a solid component, or a component that will precipitate when mixed with other components in an undiluted state, that component may be dissolved or diluted in a dilution solvent before being mixed with the other components.
[0121] Examples of dilution solvents include aliphatic hydrocarbons such as hexane, heptane, cyclohexane, etc.; aromatic hydrocarbons such as toluene, xylene, etc.; halogenated hydrocarbons such as methylene chloride, ethylene chloride, etc.; alcohols such as methanol, ethanol, propanol, butanol, 1-methoxy-2-propanol, etc.; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, cyclohexanone, etc.; esters such as ethyl acetate, butyl acetate, etc.; and cellosolve-based solvents such as ethyl cellosolve, etc.
[0122] The concentration and viscosity of the prepared coating solution may be within a range that allows coating, and may be appropriately selected depending on the situation. For example, the adhesive composition P1 is diluted so that the concentration is 10 to 60 mass%. In addition, when obtaining the coating solution, the addition of a dilution solvent or the like is not a necessary condition, and if the adhesive composition P1 has a viscosity that allows coating, it is not necessary to add a dilution solvent. In this case, the adhesive composition P1 becomes a coating solution in which the polymerization solvent of the (meth)acrylic acid ester polymer (A) is used as the dilution solvent.
[0123] The adhesive composition P2 for preparing the second adhesive can be produced in the same manner as the adhesive composition P1. For example, a polyurethane polyol is first produced, and the resulting polyurethane polyol is mixed with a polyisocyanate crosslinking agent to produce the adhesive composition P2. Additives may be added as necessary.
[0124] As described above, the polyurethane polyol is produced by reacting a polyol with a polyisocyanate. The polyurethane polyol obtained is added to a polyisocyanate crosslinking agent and a dilution solvent, and mixed thoroughly to obtain a solvent-diluted adhesive composition P2 (coating solution). Additives may be added as necessary.
[0125] (1.6. Manufacturing of Adhesives) The adhesive constituting the adhesive layer is preferably obtained by crosslinking the above-mentioned adhesive composition P1 and adhesive composition P2, respectively. The crosslinking of the adhesive composition P1 and adhesive composition P2 can usually be performed by a heat treatment. This heat treatment can also serve as a drying treatment for volatilizing dilution solvents and the like from the coating film of the adhesive composition P1 and adhesive composition P2 applied to a desired object.
[0126] The heating temperature in the heat treatment is preferably 50 to 150° C., and more preferably 70 to 120° C., in the case of the adhesive composition P1. It is preferably 50 to 150° C., and more preferably 70 to 120° C., in the case of the adhesive composition P2. The heating time is preferably 10 seconds to 10 minutes, and more preferably 50 seconds to 2 minutes, in the case of the adhesive composition P1. It is preferably 10 seconds to 10 minutes, and more preferably 50 seconds to 2 minutes, in the case of the adhesive composition P2.
[0127] After the heat treatment, a curing period of about 1 to 2 weeks may be provided at room temperature (e.g., 23°C, 50% RH) as necessary. When curing is required, the adhesives (first adhesive and second adhesive) having a crosslinked structure are obtained after the curing period has elapsed. When curing is not required, the adhesives (first adhesive and second adhesive) having a crosslinked structure are obtained after the heat treatment is completed.
[0128] (1.7. Manufacturing of adhesive sheets) The method for producing the adhesive sheet 1 is not particularly limited, and it may be produced by a known method. For example, the coating liquid of the adhesive composition P1 is applied to the release surface of one of the release sheets, and a heat treatment is performed to crosslink the adhesive composition, forming a coating layer, thereby obtaining a release sheet with a coating layer. The coating liquid of the adhesive composition P2 is applied to the release surface of the other release sheet, and a heat treatment is performed to crosslink the adhesive composition, forming a coating layer, thereby obtaining a release sheet with a coating layer. Then, the release sheet 21 with the coating layer and the release sheet 22 with the coating layer are bonded together so that both coating layers are in contact with each other. If curing is required, the coating layer becomes the adhesive layer after a predetermined curing period. If curing is not required, the coating layer becomes the adhesive layer as it is. This results in the adhesive sheet 1 having the laminate 10 in which the first adhesive layer 11 and the second adhesive layer 12 are laminated.
[0129] Examples of the method for applying the coating liquid of the adhesive compositions P1 and P2 include a bar coating method, a knife coating method, a roll coating method, a blade coating method, a die coating method, and a gravure coating method.
[0130] In this specification, when it is written "X to Y" (X and Y are any numbers), it means "X or more and Y or less" unless otherwise specified, and also means "preferably greater than X" or "preferably smaller than Y". Furthermore, when it is written "X or more" (X is any number), it means "preferably greater than X" unless otherwise specified, and when it is written "Y or less" (Y is any number), it also means "preferably smaller than Y" unless otherwise specified.
[0131] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and may be modified in various aspects within the scope of the present invention. EXAMPLES
[0132] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples.
[0133] Example 1 1. Preparation of (meth)acrylic acid ester polymer (A) 65 parts by mass of 2-ethylhexyl acrylate, 10 parts by mass of 4-acryloylmorpholine, 10 parts by mass of isobornyl acrylate, and 15 parts by mass of 2-hydroxyethyl acrylate were copolymerized by solution polymerization to prepare a (meth)acrylic acid ester polymer (A). The molecular weight of this (meth)acrylic acid ester polymer (A) was measured by the method described below, and the weight average molecular weight (Mw) was 500,000.
[0134] The weight average molecular weight (Mw) is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC) under the following conditions (GPC measurement). (Measurement conditions) GPC measuring device: Tosoh HLC-8020 GPC columns (passed in the following order): Tosoh Corporation TSK guard column HXL-H TSK gel GMHXL (×2) TSK gel G2000HXL Measurement solvent: Tetrahydrofuran ·Measurement temperature: 40℃
[0135] 2. Preparation of adhesive composition P1 100 parts by mass (solid content equivalent; same below) of the (meth)acrylic acid ester polymer (A) obtained above, 0.20 parts by mass of an isocyanate-based crosslinking agent (manufactured by Mitsui Chemicals, Inc., product name "Takenate D110N") as the crosslinking agent (B), and 0.20 parts by mass of 3-glycidyloxypropyltrimethoxysilane (manufactured by Shin-Etsu Silicones, KBM403) as the silane coupling agent (C) were mixed, thoroughly stirred, and diluted with methyl ethyl ketone to obtain a coating solution of an acrylic adhesive composition P1 with a solid content concentration of 45% by mass.
[0136] 3. Preparation of urethane polymer 100 parts by mass of trifunctional polypropylene glycol (number average molecular weight 1000), 7 parts by mass of a trimethylolpropane adduct of tolylene diisocyanate, 0.01 parts by mass of dioctyltin dilaurate, and 43 parts by mass of toluene were charged and reacted for 3 hours at 100° C. Then, when the presence of isocyanate groups could no longer be confirmed by an infrared spectrophotometer, the mixture was cooled to obtain a polyurethane polyol solution.
[0137] 4. Preparation of adhesive composition P2 100 parts by mass of the obtained polyurethane polyol and 15 parts by mass of a trimethylolpropane adduct of tolylene diisocyanate were mixed, thoroughly stirred, and diluted with ethyl acetate to obtain a coating solution of a urethane-based pressure-sensitive adhesive composition P2.
[0138] 5. Manufacturing of adhesive sheets The obtained adhesive composition P1 coating solution was applied to the release-treated surface of a release sheet (manufactured by Lintec Corporation, product name "SP-PET752150") using a knife coater so that the thickness after drying would be 100 μm. After coating, the coating was heated at 90° C. for 1 minute to promote a crosslinking reaction, thereby forming a coating layer made of an adhesive having a crosslinked structure composed of a (meth)acrylic acid ester polymer (A) and a crosslinking agent (B).
[0139] Next, the coating layer on the release sheet obtained above was attached to the release-treated surface of another release sheet (manufactured by Lintec Corporation, product name "SP-PET381130") so that they were in contact with each other. After that, the sheet was cured for 7 days under conditions of 23°C and 50% RH to obtain a first laminate having a first adhesive layer made of an acrylic adhesive (first adhesive) sandwiched between two release sheets.
[0140] Next, the obtained adhesive composition P2 coating solution was applied to the release-treated surface of a release sheet (manufactured by Lintec Corporation, product name "SP-PET752150") using a knife coater so that the thickness after drying would be 50 μm. After application, the dilution solvent was thoroughly removed by heating at 90° C. for 1 minute to form a second adhesive layer made of a urethane-based adhesive (second adhesive). The second adhesive layer on the release sheet obtained above was attached to the release-treated surface of another release sheet (manufactured by Lintec Corporation, product name "SP-PET381130") so that they were in contact with each other, to obtain a second laminate sandwiched between two release sheets.
[0141] One release sheet (SP-PET381130) was peeled off from the first laminate having the first adhesive layer to expose the first adhesive layer, and then one release sheet (SP-PET381130) was peeled off from the second laminate having the second adhesive layer to expose the second adhesive layer.
[0142] The exposed main surface of the first adhesive layer and the exposed main surface of the second adhesive layer were bonded together to obtain a coreless adhesive sheet having a laminate sandwiched between two release sheets in which the first adhesive layer and the second adhesive layer were laminated in contact with each other.
[0143] The thickness of the adhesive layer is a value measured using a constant pressure thickness measuring instrument (PG-02 manufactured by Teclock Corporation) in accordance with JIS K7130.
[0144] Example 2 An adhesive sheet was produced in the same manner as in Example 1, except that the thickness of the second adhesive layer was changed to 75 μm.
[0145] Example 3 An adhesive sheet was produced in the same manner as in Example 2, except that the thickness of the first adhesive layer was changed to 75 μm.
[0146] Comparative Example 1 Except for changing the thickness of the first pressure-sensitive adhesive layer to 150 μm and not forming the second pressure-sensitive adhesive layer, an adhesive sheet was produced in the same manner as in Example 1. That is, the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet according to Comparative Example 1 was a single layer of the first pressure-sensitive adhesive.
[0147] Comparative Example 2 A coating solution of the adhesive composition P1 was applied to one main surface of a 50 μm-thick polyethylene terephthalate (PET) film (manufactured by Toyobo Co., Ltd., product name "Cosmoshine TA063 (50 μm)") as a core material so as to have a thickness of 50 μm after drying to form a first adhesive layer made of an acrylic adhesive (first adhesive), and then a coating solution of the adhesive composition P2 was applied to the other main surface of the PET film so as to have a thickness of 75 μm after drying to form a second adhesive layer made of a urethane adhesive (second adhesive). Except for this, an adhesive sheet was manufactured by the same method as in Example 1. That is, the adhesive sheet according to Comparative Example 2 had a configuration in which a PET film as a core material was disposed between the first adhesive layer and the second adhesive layer.
[0148] Comparative Example 3 Except for changing the thickness of the second pressure-sensitive adhesive layer to 150 μm and not forming the first pressure-sensitive adhesive layer, an adhesive sheet was produced in the same manner as in Example 1. That is, the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet according to Comparative Example 3 was a single layer of the second pressure-sensitive adhesive.
[0149] The physical properties of the resulting pressure-sensitive adhesive sheet were measured as follows.
[0150] (A side adhesive strength) The adhesive strength of the first adhesive layer (adhesive strength of the A side) was measured as follows. For Examples 1 to 3 and Comparative Example 2, the release sheet on the second adhesive layer side was peeled off, and the good adhesive surface of a 100 μm-thick good adhesive PET (PET100A-4100, manufactured by Toyobo Co., Ltd.) was attached to the exposed surface of the second adhesive layer by thermal lamination (70° C., 1 m / min) to prepare a measurement sample. For Comparative Examples 1 and 3, one of the release sheets (manufactured by Lintec Corporation, product name "SP-PET381130") was peeled off, and the good adhesive surface of a 100 μm-thick good adhesive PET (PET100A-4100, manufactured by Toyobo Co., Ltd.) was attached to the exposed surface of the adhesive layer by thermal lamination (70° C., 1 m / min) to prepare a measurement sample. The measurement sample obtained above was cut into a width of 25 mm and a length of 100 mm. The release sheet was peeled off from the measurement sample under an environment of 23°C and 50% RH, and the exposed first adhesive layer was attached to soda lime glass (manufactured by Nippon Sheet Glass Co., Ltd.). At this time, the first adhesive layer was pressed by rolling it back and forth once with a 2 kg roller to attach it. After attachment, the sample was left for 24 hours under conditions of 23°C and 50% RH. After leaving it, the adhesive strength (N / 25 mm) of the first adhesive layer was measured using a tensile tester (Tensilon manufactured by Orientec Co., Ltd.) under conditions of a peel speed of 300 m / min and a peel angle of 180°. The measurement was performed under conditions other than those described here in accordance with JIS Z0237:2009. The results are shown in Table 1.
[0151] (B side adhesive strength) The adhesive strength of the second adhesive layer (adhesive strength of side B) was measured as follows. The adhesive sheets of the examples and comparative examples were cut to a width of 25 mm and a length of 100 mm to prepare a measurement sample. For examples 1 to 3 and comparative example 2, the release sheet on the second adhesive layer side was peeled off from the measurement sample obtained above in an environment of 23°C and 50% RH, and the exposed second adhesive layer was attached to soda lime glass (manufactured by Nippon Sheet Glass Co., Ltd.). For comparative examples 1 and 3, the release sheet (SP-PET381130) was peeled off from the measurement sample obtained above in an environment of 23°C and 50% RH, and the exposed second adhesive layer was attached to soda lime glass (manufactured by Nippon Sheet Glass Co., Ltd.). At this time, the second adhesive layer was pressed back and forth once with a 2 kg roller to be attached. After attachment, the sample was left for 24 hours under conditions of 23°C and 50% RH. After leaving it, the adhesive strength (N / 25 mm) of the second adhesive layer was measured using a tensile tester (Tensilon manufactured by Orientec Co., Ltd.) at a peel speed of 300 m / min and a peel angle of 180°. The measurements were performed under conditions other than those described here in accordance with JIS Z0237:2009. The results are shown in Table 1.
[0152] (Indentation depth and indentation rate) The release sheet on the second adhesive layer side was peeled off from the adhesive sheet produced in the Examples and Comparative Examples, and the exposed second adhesive layer was attached to soda lime glass (manufactured by Nippon Sheet Glass Co., Ltd.). Next, the release sheet arranged on the main surface of the first adhesive layer was peeled off to produce a laminate A having a configuration of glass plate / second adhesive layer / first adhesive layer with the first adhesive layer exposed. Similarly, a laminate B having a configuration of glass plate / first adhesive layer / second adhesive layer with the second adhesive layer exposed was produced. Using a texture analyzer (TA.XT.Plus manufactured by Stable Micro Systems), a load was continuously applied to the main surface (A surface) of the exposed first adhesive layer in the laminate A at a pressing speed of 0.01 mm / sec, and the pressing depth was measured when the load reached 5 N, which was taken as the A surface pressing depth. Similarly, the pressing depth of the main surface (B surface) of the second adhesive layer in the laminate B was measured, which was taken as the B surface pressing depth. In Comparative Example 1, since the pressure-sensitive adhesive sheet did not have a second pressure-sensitive adhesive layer, only the A-side indentation depth was measured. In Comparative Example 3, since the pressure-sensitive adhesive sheet did not have a first pressure-sensitive adhesive layer, only the B-side indentation depth was measured. The results are shown in Table 1.
[0153] From the obtained indentation depth, the ratio (indentation rate) (%) of the indentation depth to the total thickness of the laminate was calculated. In Examples 1 to 3 and Comparative Examples 1 and 3, the total thickness of the laminate was the sum of the thicknesses of the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer. In Comparative Example 2, the total thickness of the laminate was the sum of the thicknesses of the first pressure-sensitive adhesive layer, the second pressure-sensitive adhesive layer, and the core material. The results are shown in Table 1.
[0154] (Total light transmittance) The adhesive layer of the adhesive sheet obtained in the examples and comparative examples was attached to glass to prepare a measurement sample. After background measurement was performed on the glass, the total light transmittance (%) of the measurement sample was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., product name "NDH-5000") in accordance with JISK7361-1:1997. The results are shown in Table 1.
[0155] (Hayes) The haze of the pressure-sensitive adhesive sheets obtained in the examples and comparative examples was measured in accordance with JIS K7136: 2000 using a haze meter (NDH-5000, manufactured by Nippon Denshoku Industries Co., Ltd.) The results are shown in Table 1.
[0156] The pressure-sensitive adhesive sheets produced in the Examples and Comparative Examples were evaluated as follows.
[0157] (Step-following ability) A glass plate (NSG Precision, product name "Corning Glass Eagle XG", 90 mm length x 50 mm width x 0.5 mm thickness) was printed and cured using ultraviolet-curable ink on the surface to create a stepped glass plate with a frame-shaped printed step (external dimensions: 90 mm length x 50 mm width, 5 mm width, 5 μm height).
[0158] For Examples 1 to 3 and Comparative Example 2, the release sheet on the second adhesive layer side was peeled off, and the exposed second adhesive layer was attached to a glass plate (manufactured by NSG Precision, product name "Corning Glass Eagle XG", length 90 mm x width 50 mm x thickness 0.5 mm) to prepare a laminate for evaluating the step conformability. For Comparative Examples 1 and 3, one release sheet (manufactured by Lintec Corporation, product name "SP-PET381130") was peeled off, and the exposed adhesive layer was attached to a glass plate (manufactured by NSG Precision, product name "Corning Glass Eagle XG", length 90 mm x width 50 mm x thickness 0.5 mm) to prepare a laminate for evaluating the step conformability. Next, the release sheet of the laminate for evaluating the step conformability was peeled off to expose the adhesive layer. Then, using a laminator (manufactured by Fujipla, product name "LPD3214"), the exposed surface of the adhesive layer and the stepped surface of the stepped glass plate were bonded together so that the adhesive layer covered the entire frame-shaped print, and this was used as the evaluation sample.
[0159] The obtained evaluation sample was autoclaved for 20 minutes under conditions of 50°C and 0.5 MPa, and then the pressure-sensitive adhesive layer attached near the step was visually inspected and the initial step conformability was evaluated according to the following criteria. Furthermore, even after leaving the sample to stand for 12 hours in an environment of 23°C and 50% RH, the pressure-sensitive adhesive layer attached near the step was visually inspected and the step conformability was evaluated according to the following criteria. The results are shown in Table 1. A: It conforms to all uneven surfaces and there are no air bubbles or peeling. F: Air bubbles and peeling were observed in the stepped areas.
[0160] (surface conformity) The release sheet on the first adhesive layer side was peeled off from the adhesive sheets obtained in the Examples and Comparative Examples, and the exposed first adhesive layer was attached to the inside of a plastic molded plate having a curved surface of 10 mmφ. The adhesive layer after attachment was visually inspected, and the curved surface conformability was evaluated according to the following criteria. The results are shown in Table 1. A: It conforms to curved surfaces and no air bubbles, peeling or lifting are observed. E: The tape conformed to the curved surface when first applied, but after 1 minute, air bubbles and peeling were observed on the curved surface. F: Air bubbles, peeling, and no conformity to the curved surface were observed.
[0161] (Reworkability) The reworkability was evaluated as follows. The release sheet on the second adhesive layer side was peeled off from the adhesive sheets obtained in the Examples and Comparative Examples, and the exposed second adhesive layer was attached to the surface of a glass plate (manufactured by NSG Precision, product name "Corning Glass Eagle XG", length 90 mm x width 50 mm x thickness 0.5 mm). After leaving it for 10 minutes in an environment of 23°C and 50% RH, an attempt was made to peel off the second adhesive layer from the glass plate, and the reworkability was evaluated according to the following criteria. The results are shown in Table 1. A: It was easily peeled off from the glass plate, and no adhesive was left behind on the glass plate. E: The tape was easily peeled off from the glass plate, but adhesive residue was left on the glass plate. F: Adhered to the glass plate and could not be peeled off.
[0162] [Table 1]
[0163] It was confirmed from Table 1 that the pressure-sensitive adhesive sheets of Examples 1 to 3 exhibited good conformability to uneven surfaces and curved surfaces, as well as good reworkability. [Industrial Applicability]
[0164] The pressure-sensitive adhesive sheet of the present invention has good reworkability and can be suitably used, for example, for bonding members having stepped and / or curved surfaces. [Explanation of symbols]
[0165] 1...Adhesive sheet 10...Laminate 11...First adhesive layer 12…Second adhesive layer 21, 22...Release sheet
Claims
1. A pressure-sensitive adhesive sheet having a laminate in which a first pressure-sensitive adhesive layer and a second pressure-sensitive adhesive layer are laminated, when the surface of the laminate facing the first pressure-sensitive adhesive layer is designated as side A and the surface of the laminate facing the second pressure-sensitive adhesive layer is designated as side B, the adhesive strength of side A is greater than the adhesive strength of side B, A pressure-sensitive adhesive sheet in which, when side A is continuously pressed at a pressing speed of 0.01 mm / sec, the pressing depth at the time when the pressing load reaches 5 N is defined as the side A pressing depth, and when side B is continuously pressed at a pressing speed of 0.01 mm / sec, the pressing depth at the time when the pressing load reaches 5 N is defined as the side B pressing depth, the side A pressing ratio, which is the side A pressing depth relative to the thickness of the laminate, and the side B pressing ratio, which is the side B pressing depth relative to the thickness of the laminate, are 35% or more.
2. The pressure-sensitive adhesive sheet according to claim 1 , wherein the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer are in contact with each other in the laminate.
3. The pressure-sensitive adhesive sheet according to claim 1 , wherein the B-side indentation ratio is greater than the A-side indentation ratio.
4. 4. The pressure-sensitive adhesive sheet according to claim 1, wherein the ratio of the adhesive strength of the A side to the adhesive strength of the B side is within a range of 2 or more and 10,000 or less.
5. The pressure-sensitive adhesive sheet according to claim 1 , wherein the first pressure-sensitive adhesive layer has a thickness of 30 μm or more and 800 μm or less.
6. The pressure-sensitive adhesive sheet according to claim 1 , wherein the second pressure-sensitive adhesive layer has a thickness of 10 μm or more and 300 μm or less.
7. The pressure-sensitive adhesive sheet according to claim 1 , wherein the first pressure-sensitive adhesive layer is made of an acrylic pressure-sensitive adhesive, and the second pressure-sensitive adhesive layer is made of a urethane pressure-sensitive adhesive.
8. The pressure-sensitive adhesive sheet according to claim 1 , comprising a release sheet disposed on the A side and a release sheet disposed on the B side.
Citation Information
Patent Citations
Double-sided adhesive tape
JP2015131924A